Popularization of improved Mustard (Brassica juncea L.) production technology through frontline demonstrations in Pali district of Rajasthan - Singh, Dheeraj; Kumar, Chandan; Chaudhary, M. K.; Meena, M. L. (Indian Journal of Extension Education, 2018)
Front line demonstrations (FLD,s) on Mustard were laid down 20 hectare area with the active participation of 60 farmers  to demonstrate production potential and economic benefits of improved production technologies comprising high  yielding varieties namely NRCDR-2, PM-26 and PM-27 in Pali district of Rajasthan state during rabi seasons from 2012  to 2015 in rainfed farming situation. The improved production technologies recorded an additional yield ranging from  0.47 to 5.93 qha-1. The per cent increase yield under improved production technologies ranged from 27.34 to 53.66  (NRCDR-2), 3.74 to 13.84 (PM-26) and 9.16 to 37.64 (PM-27) in respective years. The average extension gap,  technology gap and technology index were 2.82 qha-1, 6.58 qha-1 and 30.32 per cent, respectively in different varieties of  mustard. The improved production technologies gave higher benefit cost ratio ranging from 2.11 to 2.86 with compared to  local checks (1.03 to 1.31) being grown by farmers under locality. The productivity of mustard per unit area could be  increased by adopting feasible scientific and sustainable management practices with a suitable variety. Considering the  above facts, frontline demonstrations were carried out in a systematic and scientific manner on farmer's field to show the  worth of improved variety and convincing farming community about potentialities of improved production management  technologies of mustard for further adoption by the farming community.
Keywords: Adoption; demonstration; impact; livelihood security; mustard